The retreatment of a mandibular second premolar with unusual canal anatomy - Pai, AEV; Gautam, S; Kundabala, M (Kathmandu University Medical Journal, 2010)
Mandibular premolars usually have a single root and canal. Complex root canal system with atypical variations is a common finding among them. Failure to identify such a one can affect the prognosis of endodontic treatment. Apart from knowledge and sophisticated instruments, a good clinical expertise is required in identifying, tracing and treating such a root canal system. This case report is on the retreatment of a left mandibular second premolar (44) having a Vertucci's Type III canal configuration. Inability to identify this canal configuration led to a missed canal, faulty obturation and post treatment apical periodontitis. DOI: 10.3126/kumj.v7i3.2741 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 298-300